2017
DOI: 10.1007/s12110-017-9284-0
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Legal Paternity for Children of Unmarried American Women

Abstract: The establishment of a legal father for children of unmarried parents reflects both high paternity confidence and male willingness to commit to paternal investment. Whether an unmarried man voluntarily acknowledges paternity after a child is born has important consequences for both the mother and child. This paper brings to bear a life history perspective on paternity establishment, noting that men face trade-offs between mating and parental effort and that women will adjust their investment in children based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The association between paternal investment and birth outcomes has been explored with the use of birth registry data. For example, establishment of paternity for children of unmarried mothers was used as a proxy for both high paternity confidence and male willingness to commit to paternal investment; it was also found to predict birth outcomes, including low birth weight [25]. Missing fathers' names in birth registry data can also be treated as a surrogate measure of a lack of paternal involvement and was found to be a risk factor of infant mortality and low birth weight [26].…”
Section: Introductionmentioning
confidence: 99%
“…The association between paternal investment and birth outcomes has been explored with the use of birth registry data. For example, establishment of paternity for children of unmarried mothers was used as a proxy for both high paternity confidence and male willingness to commit to paternal investment; it was also found to predict birth outcomes, including low birth weight [25]. Missing fathers' names in birth registry data can also be treated as a surrogate measure of a lack of paternal involvement and was found to be a risk factor of infant mortality and low birth weight [26].…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature confirms that the voluntary establishment of legal paternity by a father can be a proxy for both paternity confidence (a man’s assessment of the likelihood that he is the father of a putative child) and male commitment to investing in offspring, all of which reduces the anxiety of pregnant women [19,22]. To establish legal paternity for unmarried women, in Poland, as in many other countries, a man can voluntarily sign an Acknowledgment of Paternity form, and in such case his name will appear on the birth certificate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the internalization of Catholic values is so strong that even those who do not declare themselves to be religious, and who are not members of the Catholic Church, seem to be affected by it [71,72]. In addition, cohabitating women may not only suffer social disapproval, but may experience law-related disadvantages due to their status [19]. In more conservative countries, cohabiting couples experience different judicial outcomes in relation to social security and tax, inheritance, and welfare benefit rights [73], as compared with married couples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress may be particularly devastating when the father does not acknowledge paternity, indicated by the lack of the father’s name on the birth certificate [ 7 , 8 , 9 , 10 ]. As authors suggest, the relationship between the mother and father in these circumstances is of short duration and characterized by low paternal confidence [ 10 ], or the mother does not know who the father of her child is or does not want to identify him for many different reasons. The risks of low birth weight (LBW) and preterm birth are higher among unmarried mothers without paternal involvement compared to married couples, as has been previously reported [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%